Digital Forensics Science and Knowledge Organization An Interdisciplinary Approach to Addressing the Conceptual Challenges of Born-Digital Records - Montoya-Mogollón, Juan Bernardo [UNESP]; Troitiño, Sonia [UNESP] (Nomos Verlag, 2020)
The digital age has drastically impacted the way people think and act using technology. The advancements of the 20th and 21st centuries have ushered in a number of changes related to the treatment of information. Private and public organizations have faced increasing pressure to shift to digital formats. However, the speed at which these changes have occurred has created several conceptual concerns related to the trustworthiness of digital records and systems, and the security afford by their infrastructure. This paper identifies and addresses several of these concerns through the interdisciplinary theoretical frame of Archival, Diplomatic, and Digital Forensics areas. This alternative approach is presented as a contribution to Knowledge Organization (KO), which can help reframe the way scholars understand the following problems posed by digital records: 1) The challenge of maintaining digital records as authentic, accurate, and reliable sources of information; 2) The challenge of establishing trustworthy repositories for information storage and access; and 3) The challenge of ensuring long-term maintenance and preservation of records. We argue that the different concepts and techniques of Archival Diplomatics and Digital Forensics, such as provenance, original order principles, and chain of custody, have much to contribute to the professional study and practice of KO in digital environments, particularly where it relates to issues of authenticity.